Solitons and conservation laws to the resonance nonlinear Shrodinger's equation with both spatio-temporal and inter-modal dispersions - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi (Elsevier Gmbh, 2017)
The resonant nonlinear Shrodinger's equation (RNLSE) with both spatio-temporal (STD) and inter-modal (IMD) dispersions which describes the modelling of fluids and propagation dynamics of optical solitons is studied using three analytical schemes. These are generalized projective-Riccati equation method (GPRE), Bernoulli sub-ODE method and the Riccati-Bernoulli sub-ODE. The presented problem is studied with Kerr law nonlinearity. Dark optical, singular, and combined formal solitons are acquired. The constraint conditions that naturally fall out of the solution structure guarantee the existence of these solitons. We derive the Lie point symmetry generators of a system of partial differential equations (PDEs) obtained by decomposing the underlying equation into real and imaginary components. Then we used these symmetries to construct a set of nonlocal conservation laws (Os) using the technique introduced by Ibragimov. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Optical solitons; STD; Lie symmetries; Cls